Monthly Electrical Energy Consumption Modeling Using Ant Lion Optimizer - Sagliyan, Ozge; Colak, Ayse; Yeşilbudak, Mehmet (IEEE, 2019)
This study concentrates on the application of ant lion optimizer in the monthly electrical energy consumption modeling. For this purpose, daily electrical energy consumption recorded for spring and summer seasons of Turkey is used as the output variable. For the same time period, daily average temperature, daily average wind speed, daily average humidity, daily average rainfall and daily total global solar radiation are utilized as the input variables affecting the electrical energy consumption. Many efficient consumption models are developed on the monthly basis and their modeling results are extensively compared in terms of different accuracy measures. In both seasons, commonly, the electrical energy consumption curves estimated by the ant lion optimizer-based exponential model shows good agreement with the actual ones.
Keywords: Consumption; Electrical energy; Modeling; Metaheuristic optimization